Aplikasi Ekstrak Daun Sirih (Piper betle L.) sebagai Sabun Antijerawat - Nurilliyyin Akib; Amirul Mu'min; Andi Nafisah Tendri Ajeng; Nurhijrianti Akib; Rifa'atul Mahmudah; Halik Halik (Program Studi S2 Kesehatan Masyarakat Universitas Halu Oleo, 2024)
This study was about the anti-acne transparent soap that contains extracts of betel leaves (Piper betle L.). This study aimed to determine the physical properties and the preference level of the panelists to transparent soap that contains extracts of betel leaf (Piper betle L.). Betel leaves extract obtained by maceration method using 96% ethanol and dilapidated using liquid solvent with n-hexane and 96% ethanol. Betel leaves extract formulated into dosage transparent soap with a variation of concentration 2%, 4% and 6%. Transparent soap tested their physical properties at weeks 1, 2 and 3 included the ability to form foam and pH values. The hedonic levels of transparent soap tested to the 30 panelists included preference for transparency, foam, and an image before and after use. The results showed that transparent soap formulation obtained a good texture and transparency. The test results showed high physical properties obtained transparent soap bubble around 6.4 to 6.5 cm and pH of transparent soap about 9.4 to 9.5 where it was in accordance with the Indonesian National Standard (SNI).